Literature Review: The Relationship between Exercise Habits and the Level of Primary Dysmenorrhea in Adolescent Girls - Ridha Auliasyfa Nabillah,; Auliasyfa Nabillah, Ridha; Wibisono, AYG (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
Exercise habits have been proven effective in reducing the intensity of menstrual pain (dysmenorrhea) in adolescent girls. Unfortunately, many teenagers are still lacking exposure to information about the benefits of exercise for reproductive health. According to the World Health Organization (WHO), around 90% of women experience dysmenorrhea, with a significant portion experiencing severe pain. Based on data from the Indonesian Ministry of Health in 2020, 107,673 women (64.24%) experienced primary dysmenorrhea, while 9,496 (9.63%) experienced secondary dysmenorrhea. A study conducted by the Banten Provincial Health Office and BPS in 2023 revealed that 60.19% of 10,000 adolescents in Banten suffered from dysmenorrhea. In Tangerang City, among 134 adolescent girls experiencing primary dysmenorrhea, 102 individuals (76.1%) reported moderate pain, and 32 individuals (23.9%) experienced severe pain. Objective: To analyze research findings from the past five years regarding the relationship between exercise habits and levels of primary dysmenorrhea. Method: A literature review was conducted based on national and international journals obtained through Google Scholar using the keywords: exercise habits, primary dysmenorrhea, adolescent girls. Articles were selected according to predetermined inclusion and exclusion criteria within the 2021–2025 range. Results: Of the 10 articles analyzed (5 national journals and 4 international journals), the majority showed a relationship between exercise habits and the intensity of menstrual pain in adolescent girls. One national journal found no significant relationship. Conclusion: Primary dysmenorrhea is a common health issue among adolescent girls that affects quality of life. Non-pharmacological interventions such as yoga, pilates, and regular exercise are proven to effectively reduce menstrual pain intensity. Healthy lifestyle factors including maintaining BMI, regular physical activity, balanced nutrition, and anemia prevention play an important role. Health education about lifestyle should be enhanced, especially in school environments.